Preliminary Analysis of a Youth Soccer Talent Identification Program in North Sumatra - Irvan Abdillah; Ahmad Nasrulloh (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2026)
Youth soccer talent identification programs are foundational to long-term athlete development, yet systematic empirical scrutiny of regional programs in developing countries remains limited. To address this, a preliminary analysis was conducted using a descriptive mixed-methods design, drawing on field observation, official athlete registry documents, quarterly physical condition reports, and competition records from 18 active male athletes aged 15–17 years. A complete absence of Q3-born athletes (July–September) was confirmed statistically significant via binomial test (p = .006, w = .577), suggestive of maturational bias consistent with the Relative Age Effect. While explosive power improved consistently across all position groups, aerobic capacity (VO2Max) remained largely stagnant throughout the monitoring period. Beyond physical development, technical assessment relied predominantly on subjective coach evaluation without standardized instruments, limiting the objectivity of talent identification decisions. These gaps across selection methodology, aerobic development, and assessment objectivity collectively justify a full-scale CIPP evaluation, which should employ structured interviews, validated questionnaires, and direct observation across all four CIPP components to generate evidence-based program improvement recommendations.